Prevalence of Signs and Symptoms of Pseudotumor Cerebri Syndrome Before and After Transsphenoidal Surgery for Cushing’s Disease – A Prospective Consecutive Case Series - Huckhagel, Torge; Flitsch, Jörg; Rotermund, Roman; Knospe, Volker (Experimental and Clinical Endocrinology & Diabetes, 2020)
Introduction Pseudotumor cerebri syndrome (PTCS) has anecdotally been described after successful treatment of Cushing’s disease (CD), but the prevalence following transsphenoidal surgery has not been determined so far in a prospective study.Patients and Methods 41 consecutive adult CD patients were prospectively screened for signs and symptoms of PTCS, headache-related impairment, and ophthalmological features associated with intracranial pressure elevation before surgery and at follow-up (mean 4 months).Results Biochemical remission was achieved in 36 of 41 (87.8%) patients after surgery. The most frequent preoperative complaints were visual acuity impairment (19 cases; 46.3%), headache (13 cases; 31.7%), and ear noise (9 cases; 22.0%). A significant reduction of visual disturbances was seen at follow-up. Overall, CD patients presented with fairly low headache-related emotional and functional restrictions before and after surgery. One of 34 (2.9%) patients with sufficient ophthalmological follow-up showed new-onset papilledema combined with temporary worsening of visual acuity and scotoma.Conclusion Our results suggest a very low frequency of signs and symptoms of PTCS after surgical treatment for CD in adults. This estimate is in line with previous outcomes from retrospective pediatric CD series. Further large-scale studies are needed to determine the actual prevalence of this condition following biochemical remission of CD.
Keywords: Pituitary adenoma<Cancer; Glucocorticoids<Hormones; Hypopituitarism<Insufficiencies